Private Activity in Transport Shows Strong Growth in 2006 - World Bank (Washington, DC, 2012)
This note states that the number of new transport projects with private participation, along with the associated investment commitments, grew strongly for the second consecutive year, according to just-released data from the Private Participation in Infrastructure Project Database.